"99.9% effective": calculating credibility and consuming trust in antibacterial promises. Issue 4 (3rd July 2016) - Kim, Gloria C.S.
ABSTRACT: This article introduces the phrase "99.9% Effective" – the claim brandished on all manner of antibacterial hand sanitizers – as a contemporary marketplace icon. It establishes the contexts of global contagious risk in which antibacterial hand sanitizers' "99.9% Effective" claim proliferates and becomes a marketplace icon. Beginning from the premise that there is no separation between our material consumption of hand sanitizers and our consumption of the cultures of the antibacterial promise, it analyzes the material meaning of this marketplace icon. Situated amid a backdrop of quotidian but potentially catastrophic twenty-first century systemic microbial risk, this article uncovers the relationship between conditions of trust, the cultures of calculation and the work of consuming this marketplace icon.